Tingkat Kepatuhan Remaja Putri dalam Mengonsumsi Tablet Tambah Darah di SMK Abdurrab Pekanbaru - Norlita, Wiwik; Isnaniar; Hardiyanti, Resti (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2023)
Compliance is a change in behavior from behavior that does not obey the rules to behavior that obeys the rules. This compliance issue refers to the government's program regarding the strategic plan of the Indonesian Ministry of Health, in which the government recommends giving iron tablets to young women. There is data that 98.6 percent of young women are not compliant in consuming iron tablets as recommended by health workers. The classic reasons found in the disobedience of young women in taking iron tablets are forgetting to take them, being lazy, and feeling unnecessary. The purpose of this study was to determine the level of adherence of young women in consuming iron tablets at SMK Abdurrab Pekanbaru. This type of research used is descriptive method. The population in this study amounted to 308 students with a sample of 75 students who were taken as respondents by Stratified Random Sampling. The instrument used in this research is a questionnaire. The results showed that the level of adherence of young women in consuming iron tablets at SMK Abdurrab Pekanbaru, 5 respondents (6.6 percent) had a high level of compliance, 2 respondents (2.7 percent) had a moderate level of compliance, and 68 respondents (90.7 percent) had a low level of compliance. From this study, it was found that most of the young women at SMK Abdurrab Pekanbaru had a low level of compliance.